Effects of soil management on the arbuscular mycorrhizal fungi in fall-sown crops in Mediterranean climates - Brito, Isabel (2006)
Soil tillage may markedly reduce the rate of arbuscular mycorrhiza (AM) establishment by breaking up the living AM fungal mycelium in the soil. In no till or reduced till management, this mycelium can allow earlier AM formation. Work under field conditions in a Mediterranean climate clearly confirmed that wheat plants cultivated under no-till system had a 6 fold greater mycorrhizal colonization than those grown using a conventional tillage system. Pot experiments were initiated to determine the benefit of the timing of colonization on plants. Soil disturbance induced by tillage practices was simulated by passing the soil through a 4 mm sieve at the start of each successive period of 3 weeks plant growth cycles. After 4 cycles of plant growth (wheat), significant effects in all colonization parameters were detected. Arbuscular, vesicular and hyphal colonization were clearly higher in undisturbed soil. To gain a global overview of the diversity of Glomeromycota under the 2 cultivation systems in the experimental field, rDNA sequences from the fungi have been amplified successfully from DNA extracted directly from field soil. In total 87 sequences were analysed, half from each kind of soil (undisturbed and disturbed). Based on differences observed in the frequency of the ribotypes present in soils under different tillage treatments, the results support the view that AMF are differently vulnerable to soil disturbance, not only in terms of diversity, but also in terms of the community structure.